Automated design methodology for automobile side panel die using an effective optimization approach - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 2007)
In this study, two approaches are proposed to improve formability of an automobile side panel. In the first approach, the effect of using double binder on springback, wrinkling and thickness reduction is studied. In the second approach, the use of optimization method in further improving formability of the automobile panel is investigated. With the optimization method, the most appropriate values of forming process parameters are calculated for optimum formability characteristics. Positions of the upper die and draw-bead, draw-bead radius, forces applied on the upper die surface and double binder surfaces are considered as process parameters. In finding optimum values, finite element analysis, response surface methodology and genetic algorithm are integrated. To achieve efficient and effective integration, a computer program is written. From this study it is observed that double binder with an appropriate stamping force improves formability significantly. Application of optimization method also improves further formability characteristics of the automobile panel. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: SHEET